Effectiveness of Effleurage Back Massage and Slow Deep Breathing on Vital Signs in Hypertension Patients - Sepdianto, Tri Cahyo; Suprajitno, Suprajitno; Ciptaning Tyas, Maria Diah (Health Gate, 2024)
There are quite a lot of hypertension sufferers in middle age in society and are easy to detect. Controlling hypertension requires lifelong medication and non-pharmacological measures. To reduce the side effects of treatment, non-pharmacological measures are needed, namely effleurage back massage and slow deep breathing. This study aimed to assess the effectiveness of effleurage back massage and slow deep breathing on vital signs, oxygen saturation, and anxiety in primary hypertension sufferers aged 45 - 54 years. The method in this research uses a quasi–experimental design with a non-randomized pretest–posttest control group design approach. The sample for this study was primary hypertension sufferers aged 45 - 54 years who received routine treatment at the Health UPTD in the Blitar City area, totaling 101 sufferers (51 in the treatment group, 50 in the control group). Inclusion criteria for patients were having systolic blood pressure of 140 – 180 mmHg and diastolic 90 – 100 mmHg, receiving a maximum of 2 standard antihypertensive treatments and not smoking. Analysis used descriptive and t-tests. The results of this study showed that after effleurage back massage and slow deep breathing, there was a decrease in systolic blood pressure of 16.37 mmHg, diastolic blood pressure of 10.39 mmHg, pulse of 3.53 times/minute and respiration of 0.73 times per minute. Effleurage back massage and slow deep breathing are effective if done regularly and require a massage break after the sixth appointment.